THE INFLUENCE OF ORGANIZATIONAL COMMUNICATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE BY BITTE - Mirta Aprilia Yuzrinda*; Andi Heru Susanto (Count : Journal of Accounting, Business and Management, 2024)
This study aims to analyze the influence of organizational communication and work environment on employee performance. This research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to 130 respondents, with 95 valid responses for analysis. The sampling technique used probability sampling with the simple random sampling method. Data analysis was conducted using SPSS 23.0, including normality tests, multicollinearity tests, heteroscedasticity tests, and both simple and multiple linear regression analyses. The findings indicate that effective organizational communication and a conducive work environment significantly and positively impact employee performance. Clear and open communication, along with a supportive work environment, enhances employee motivation and productivity. Therefore, this study recommends that companies improve their communication systems and establish a comfortable work environment to optimize employee performance.